2021
DOI: 10.3390/nano11112888
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coating and Size of Magnetic Nanoparticles on Cellular Uptake for In Vitro MRI

Abstract: Iron oxide nanoparticles (IONPs) are suitable materials for contrast enhancement in magnetic resonance imaging (MRI). Their potential clinical applications range from diagnosis to therapy and follow-up treatments. However, a deeper understanding of the interaction between IONPs, culture media and cells is necessary for expanding the application of this technology to different types of cancer therapies. To achieve new insights of these interactions, a set of IONPs were prepared with the same inorganic core and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…It is found to be superior method for manufacturing hybrid nanoparticles from uncoated IONPs. Belén Cortés-Llanos et al [ 18 ] reported the effect of coating and size of IONPs in the magnetic resonance imaging (MRI). They have prepared IONPs with inorganic core and different coatings to examine the aggregation and interactions in the physiological media together with cell levelling efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It is found to be superior method for manufacturing hybrid nanoparticles from uncoated IONPs. Belén Cortés-Llanos et al [ 18 ] reported the effect of coating and size of IONPs in the magnetic resonance imaging (MRI). They have prepared IONPs with inorganic core and different coatings to examine the aggregation and interactions in the physiological media together with cell levelling efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should merge the local effects depending on individual vessels that are reported here with a wider scope that comprises an integrative representation of the overall tumour along with its vascular system. A modelling scenario describing such a system will allow for the in silico testing of traditional therapies like radiotherapy and hyperthermia, but also novel approaches such as the internalisation of nanoparticles [57] and immunotherapies [58].…”
Section: Discussionmentioning
confidence: 99%
“…A possible interpretation for why the higher concentrations of the Fe 3 O 4 -FA NPs is more effective in inhibiting aggregation formation, can be made through looking at the interactions occur between the NPs and the amyloid aggregation under the low pH condition (which was applied to drive the aggregation formation), because increasing the concentration of the NPs under low pH, increases the iron atom concentrations, which leads to decrement in oxidation by decreasing the ratio of Fe + 2 (magnetic) to Fe + 3 (maghemite) [39,40] (because maghemite is more stable against oxidation at high temperature and different pH ranges than magnetic), [40] thus, the high-concentration samples will not become oxidated and thus they will not gain oxygen and electrons, on the other hand, decreasing the concentrations under low pH, promotes oxidation of the surface of the Fe 3 O 4 -FA NPs by increasing the Fe + 2 : Fe + 3 ratio and therefore, enhances the magnetic form, which is not stable against oxidation. Thus, the FA-Fe 3 O 4 NPs gain more oxygen and electrons, and their surface charges become more negative as compared with their high-concentration counterparts; [39,40] considering that all proteins (including amyloid beta protein) have more a nity to bind to more positive surfaces than negative ones , [41] therefore, the lowconcentration nano particles would have less interaction with amyloid beta proteins, and hence, would not be able to remove all of the amyloid aggregations, whereas the high-concentration samples can have more interactions with the amyloid beta aggregations, and hence, eliminate them e ciently.…”
Section: Discussionmentioning
confidence: 99%